Analysis of the Public Prosecutor's legal considerations in the criminal prosecution of child sexual intercourse by educators - Aziz Tri Afriko; Sinung Mufti Hangabei; Riri Tri Mayasari; J.T. Pareke (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
The purpose of this research is to analyze the juridical basis used by Public Prosecutors in formulating criminal charges and to assess its conformity with the principles of justice and child protection. The research method employed is normative legal research, utilizing statutory, case, and conceptual approaches. Data were collected through library research and analyzed qualitatively. The results of the study indicate that in formulating criminal charges, the Public Prosecutor does not merely focus on the normative fulfillment of the elements of the offense but also considers the power relation between the perpetrator and the victim, the perpetrator’s position as an educator, as well as the psychological and social impacts on the victim. The criminal charges are constructed systematically by linking legal facts, evidence, and relevant legal norms. The conclusion of this study shows that the juridical considerations of the Public Prosecutor reflect a proper application of law and are oriented toward victim protection. However, there is still a need to strengthen the integration of a restorative justice approach to achieve more substantive justice.